ACSM Expert Consensus Statement on Exertional Heat Illness: Recognition, Management, and Return to Activity. Issue 9 (September 2021) - Roberts, William O.; Armstrong, Lawrence E.; Sawka, Michael N.; Yeargin, Susan W.; Heled, Yuval; O'Connor, Francis G.
Abstract : Abstract: Exertional heat stroke (EHS) is a true medical emergency with potential for organ injury and death. This consensus statement emphasizes that optimal exertional heat illness management is promoted by a synchronized chain of survival that promotes rapid recognition and management, as well as communication between care teams. Health care providers should be confident in the definitions, etiologies, and nuances of exertional heat exhaustion, exertional heat injury, and EHS. Identifying the athlete with suspected EHS early in the course, stopping activity (body heat generation), and providing rapid total body cooling are essential for survival, and like any critical life-threatening situation (cardiac arrest, brain stroke, sepsis), time is tissue. Recovery from EHS is variable, and outcomes are likely related to the duration of severe hyperthermia. Most exertional heat illnesses can be prevented with the recognition and modification of well-described risk factors ideally addressed through leadership, policy, and on-site health care.